Effective screen reading : manage e-mail and the Internet more efficiently - Toikka, Tarmo (HRD Press, 2008)
Did you know reading text on a computer screen can be as much as 30 percent slower with less comprehension than reading printed text? Reading electronic text, e-mails and Web pages on a computer screen is different. That's why this book is important no matter what industry you are inches Effective Screen Reading provides tried-and-tested principles for increasing your on-screen productivity and effectiveness. The easy-to-handle and quick-reference guide is the first book to address fast and effective reading and learning via the computer screen. Learn various techniques for better using your vision skills. Find out why sitting correctly in front of the screen is critical. Discover how to improve concentration and understanding of what you read. Examine e-mail folder structure and filing principles. The book is organized into five chapters which include a preview of the goals of the chapter and topics to be covered and a summary of the highlights.